Hypokalemia After Rituximab Administration in Steroid-Dependent Nephrotic Syndrome: A Case Report - Guzzi, Francesco; Giovannini, Mattia; Errichiello, Carmela; Liccioli, Giulia; Mori, Francesca; Roperto, Rosa Maria; Romagnani, Paola (Frontiers in Pharmacology, 2020)
The monoclonal antibody rituximab is a commonly used steroid sparing agent for steroid-dependent idiopathic nephrotic syndrome of childhood. With this brief report, we describe the first case of symptomatic hypokalemia after intravenous rituximab administration in a young woman. The sudden onset of dizziness and palpitation prompted acute life-threatening hypokalemia recognition by blood gas analysis and electrocardiography. Her symptoms were rapidly controlled by intravenous potassium administration. Such adverse drug reactions, when mild and self-limiting, can easily be overlooked if not expected or investigated. Health professionals should take into account the possibility of acute hypokalemia after rituximab administration in order to promptly setup the appropriate treatment and limit potentially severe complications.